Ornamental Aquatic Plant Production in Florida - Eric J. Cassiano; Lyn A. Gettys (EDIS)
Florida has a unique and diverse aquaculture industry consisting of ornamental fish, food fish, shellfish, alligators, aquatic plants, and more.  Although some aquatic plants are produced for food or wetland restoration, most aquatic plant production in Florida is for the water garden and aquarium industries.  There are over 1000 different species and varieties of ornamental aquatic plants produced in Florida.  Since most ornamental aquatic plants are tropical in origin, Florida’s warm climate makes it ideal for growing them year-round.  This publication covers ornamental aquatic plant production in Florida including permitting and licensing, production techniques, farm design, pests and diseases, and marketing.